Comment card - Daniels, Jim 1956- (Carnegie Mellon University Press, 2024)
"A poetry collection that hunts for meaning in the ordinary and astonishing.Comment Card offers up a world of juxtapositions, searching for equilibrium between the sublime and the mundane: a man watching young lovers kiss while poisoned ants rain down on his porch. A Christmas tree-needle collection and Jimmy Durante. The litter of a three-hole punch and a daughter leaving for college. Tamarinds and the International Space Station. A crushed snail and the Holy Trinity. These poems wonder, how did we get here, and, by the way, where are we?"
Keywords: POETRY / American / General; poetry